Resistance to Opportunities of Plastic Recycling - He, Weiling; Layton, Astrid C; Creasy, Terry S; Borges, Alejandro (Enquiry The ARCC Journal for Architectural Research, 2021)
Plastics present a vast and pressing issue in modern society. Currently recycling efforts fall dangerously short of dealing with even a small percent of the millions of tons of plastic waste produced yearly across the globe. This article investigates resistance toward plastic recycling in three areas from both a contemporary and a historical context, highlighting the magnitude of the problem and the insufficient nature of current solutions. The three primary areas covered are the plastics problem from (1) a design perspective, (2) a material science perspective, and (3) a systems perspective. Solutions are proposed that emphasize a synergistic collaboration across disciplines and research modes. Ultimately, the conclusions point to a need for stronger engagement at the level of people (both consumers and decision makers) and reintegrating reused and recycled plastics into everyday life to build a solid foundation for success.